PERENCANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KONTEMPORER DI INDONESIA - Fathiyyah Putri Pasaribu; Muhammad Ersyad Anshari, Rahma Dona, Wedra Aprison (Adisam Publisher, 2024)
Education is a form of process from experience, with the power of education it can help growth without being limited by humans. Allah has given humans the advantage of a mind that other creatures do not have and to manage this education, education is needed, namely through learning. The purpose of writing this article is to provide an overview of planning for contemporary Islamic religious education in Indonesia today. Namely, it can be seen from a madrasah, Islamic boarding school, Islamic boarding school and college. Education today is not only related to education but is also involved in political, social and cultural factors in Indonesia which can be taken into consideration in Indonesian education. This research uses a descriptive method to analyze contemporary Islamic religious education planning in Indonesia. Data was obtained through a literature review. Planning for contemporary Islamic religious education in Indonesia should refer to and adapt to the growth and development of the times and technology. Therefore, it is necessary to develop and plan an education system with a global perspective, so that every Islamic religious education can always exist in responding to and facing every global challenge and need.